What Does Financial Institution Termination of Employment Mean in Terms of Labor Law? - Suwinto Johan; Luo Yuan Yuan (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2023)
Termination of employment or layoffs hits workers’ psychological condition hard. Layoffs commonly occur and have raised concern in global community, especially in the financial industry. Various factors trigger layoffs, including actions from banks and the Covid-19 pandemic. In that era, banks faces risk such as triggering a decrease in financing, non performing loan and etc.This study discusses layoffs that occur in financial institutions using a normative juridical method. Primary data, secondary data and other data were collected and analyzed, which results showed that layoffs mostly occur following the declines in company performance and transactions occurring from corporate actions. The labor law guarantees workers under fixed-term employment contract to be entitled to the remaining term of his work agreement when layoffs occur. However, if the work contract is not extended, no compensation will be given. This scheme distinguishes permanent workers from contract workers.